European Union law. Cases and materials. 2nd ed - Chalmers, Damian; Davies, Gareth; Monti, Giorgio (Cambridge, 2010)
"This eagerly awaited new edition has been significantly revised after extensive user feedback to meet current teaching requirements. The first major textbook to be published since the rejuvenation of the Lisbon Treaty, it retains the best elements of the first edition – the engaging, easily understandable writing style, extracts from a variety of sources showing the creation, interpretation and application of the law and comprehensive coverage. In addition it has separate chapters on EU law in national courts, governance and external relations reflecting the new directions in which the field is moving. The examination of the free movement of goods and competition law has been restructured. Chapter introductions clearly set out what will be covered in each section allowing students to approach complex material with confidence and detailed further reading sections encourage further study. Put simply, it is required reading for all serious students of EU law."